Inhibitors to change: a case study of teacher change in a rural African context - Stiles, Kathy Greaves (Rhodes University, Faculty of Education, Department of Education, 1996)
Environmental education is taught as part of the Primary School Environmental and Agricultural Science (EAS) curriculum in Zimbabwe. An attempt to improve the quality of learning in EAS resulted in a research project at the University of Zimbabwe that aimed to transpose innovative constructivist pedagogy from a western context to a rural African one. This writer has used a definition of teacher change as social change and a belief that sustainable pedagogical change involves a transformative process. The research backs up previous findings that failure to recognise and deal with how people actually experience the change process, accounts for much failure of social change. This qualitative research has attempted to provide some understanding of the complex interrelationships of factors that affected expected change in teaching style. By focusing on the process of teacher change within innovation, this researcher was able to identify inhibitors to change that were subsequently critically reflected on by the tea~hers themselves. The disappointing resistance to change first noted within the project has become a source of unexpected but potentially important illuminative understanding of teacher education and development in a non-western environment.
Keywords: Education, Elementary -- Zimbabwe; Educational change -- Zimbabwe; Environmental education -- Study and teaching (Elementary) -- Zimbabwe; Teachers -- Training of -- Zimbabwe